PENDEKATAN RUHIYAH DAN PEMBENTUKAN KARAKTER INSAN KAMIL - Arisman Arisman (Fitrah, 2020)
This article aims to discuss the spiritual approach and the formation of the character of the Muslim man and woman. Efforts to guide and direct mental development and physical growth in the sense of education cannot be separated from psychological understanding because the work of educating is dealing with humans who have stages of development, both mental and physical. The material for the approach of Lukman Hakim includes monotheism, morality, and worship. Human characteristics as human beings include; 1) Physically Healthy and Strong and Skilled, 2) Smart and clever. 3) High quality spiritual.